Energy system modeling: Public transparency, scientific reproducibility, and open development. (April 2018) - Morrison, Robbie
Abstract: A mid-2017 survey shows that 28 energy system modeling projects have made public their source code, up from six in 2010, and none in 2000. Another six web-based energy sector database projects and nine hybrid projects were established during this same period, some explicitly to service open modeling. Three distinct yet overlapping drivers can explain this shift in paradigm towards open methods: a desire for improved public transparency, the need for genuine scientific reproducibility, and a nascent experiment to see whether open source development methods can improve academic productivity and quality and perhaps also public trust. The associated source code, datasets, and documentation need suitable open licenses to enable their use, modification, and republication. The choice for software is polarized: teams need only consider maximally permissive (ISC, MIT) or strongly protective (GPLv3) licenses. Selection is influenced by whether code adoption or freedom from capture is uppermost and by the implementation language, distribution architecture, and use of third-party components. Permissive data licenses (CC BY 4.0) are generally favored for datasets to facilitate their recombination and reuse. Official and semi-official energy sector data providers should also prefer permissive licensing for copyrightable material. Highlights: Growing calls for policy-based energy system models to be "opened up". Energy system modeling projects are adopting open source development methods. Energy system database projects are co-evolving to serve datasets to open models. Source code distributed under standard copyright cannot be legally used, built, or run. Source code and datasets distributed under standard copyright cannot be republished.